Towards intelligent and integrated architecture for hydrogen fuel cell system: challenges and approaches - Guo Xiaoyu; Dong Zhen; Shen Jiabin; Xu Yiqiao; He Qiaohui; Zhao Xiaowei (National Science Open)
The hydrogen fuel cell is rapidly attracting research interest for its potential in power generation and electrified transportation. The fuel cell stack (FCS) is a complex system comprising multiple coupled subsystems, and in order to maximize the utilization of an FCS, the system-level design and control can be optimized through modeling, data-based analytics and monitoring. To this end, a systematic overview of the system architecture and control of hydrogen fuel cells is provided in this review, with focus on integration and intelligence. Firstly, the fuel cell subsystems, namely the cathode, anode and cooling loops are reviewed, where their respective control methods and impact on FCS performance are discussed. DC/DC converters are another core component of FCS, and we present an overview of fuel cell DC/DC converter topologies and integrated control of DC/DC converter and air compressor. Finally, the system-level integration of fuel cells in power systems is surveyed. In the conclusions, we discuss the challenges and perspectives concerning the integrated architecture and intelligent control for FCS, including cohesive dynamic models, data-based approaches, and integrated hardware architecture.